Potret Pelaksanaan Program Makan Bergizi Gratis di SDN Pesantren Kecamatan Mijen Kota Semarang - Azka, Maulida Fikrotul; Rahmahyani, Rahmahyani Putri; Nafiah, Lailatun Putri; Putri, Linda Amelia; Fathurrahman, Moh. Amelia; Wijayama, Bayu (Peneliti.net, 2025)
Nutrition issues in Indonesia are still a serious concern as they have a direct impact on the quality of human resources, especially in school-age children. The Free Nutritious Meal Program (MBG) was initiated during the Prabowo Subianto administration as an effort to reduce malnutrition and improve the quality of national education. This study aims to analyze the implementation of the MBG Program at SD Negeri Pesantren, Mijen Subdistrict, Semarang City, find out the students' response to the program, its impact on students' learning spirit, and the obstacles faced in its implementation. The research method used is descriptive qualitative with data collection techniques through observation, questionnaires, interviews, and documentation. The results showed that the majority of students responded positively to the MBG program by feeling happy, feeling more enthusiastic about learning, and being helped from the family's economic side. However, some obstacles were also found, such as the variety of food flavors that were not suitable for students' tastes, food portions that were considered insufficient, and distribution that was not fully equitable. Nevertheless, the MBG program is considered to have a positive impact on students' enthusiasm for learning and needs to continue to be developed with improvements in the technical aspects of its implementation.